EFICIENCIES IN THE SYSTEM OF STABILITY AND PERESTROYING IN UZBEKISTAN’S COMPREHENSIVE SCHOOLS DURING THE SOVIET GOVERNMENT (TAMADDUN NURI JURNALI, 2025)
This article provides a comprehensive analysis of the problems in the field of education during the period of stagnation and perestroika in the system of general education schools of Uzbekistan during the Soviet government. It examines how factors such as centralized management, ideological influence, lack of resources, and obsolescence of infrastructure negatively affected the quality of education in the system of the system of stagnation (1960-1980s). At the same time, the attempts to implement educational reforms during the period of perestroika (1985-1991), but their inefficiency, financial difficulties and the emergence of new shortcomings due to socio-political instability are discussed. The article presents statistical data, monitoring results, tables and analyses based on historical documents. The study draws profound conclusions based on pedagogical and historical literature to shed light on the state of the education system during these periods.